SOSIALISASI MEDIA POP UP PADA SEKOLAH DASAR NEGERI 15 KOTO LALANG KECAMATAN LUBUK KILANGAN DI KOTA PADANG - Masrizal Masrizal; Muhammad Alfarezi; Ade Betasril; Trif Vando Rahmalber (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2023)
Environmental factors play a crucial role in influencing public health, including the spread of diseases like Covid-19. Infectious diseases can affect individuals of all ages. Based on data from the Padang City Health Department, in 2019, there were 2130 reported cases of Covid-19 in various schools in Padang City. This underscores the significance of environmental factors in public health. The primary goal of this community engagement program is to enhance the understanding and awareness of teachers and students at SDN 14 Koto Lalang and SDN 15 Koto Lalang, located in the Lubuk Kilangan District, Padang City, West Sumatra Province, regarding Covid-19 prevention. This initiative involves team discussions to plan the program details and the dissemination of educational materials to teachers through pop-up books and informative leaflets. The pop-up books cover two crucial topics: proper handwashing with soap and the promotion of healthy eating, accompanied by informative leaflets. This engagement effort involved 23 teachers who displayed remarkable enthusiasm and actively participated by asking questions after the material presentations. Subsequently, they were provided with essential resources such as soap, masks, leaflets, and face shields to promote health practices within the school environment. Implementing similar strategies to raise awareness, such as educational materials and hygiene support, can significantly contribute to the well-being of students and the community. Collaborative efforts among teachers, students, and the broader community in adhering to Covid-19 prevention measures will play a vital role in maintaining public health and upholding the quality of education.